Evaluation of morphology and biventricular cardiac function in children with congenital zika syndrome. (3rd October 2022) - Barbosa, I C Q; Gomes, L P; Barbosa, A; Botelho, L F B; Montenegro, C M; Barbosa, B R C; Vilela, A T; Melo, A S O; Salemi, V S
Abstract: Introduction: The infection caused by the Zika virus during pregnancy causes microcephaly and brain damage in fetus, and the systemic involvement with diffuse muscle impairment, high frequency of arthrogryposis and microphthalmia, characterizes congenital Zika syndrome (CZS). The cardiac impairment in CZS was rarely evaluated. Purpose: To evaluate the morphology and biventricular cardiac function in children affected by CZS, using electrocardiogram (EKG), echocardiogram and biomarkers dosage. Methods: This is a cross-sectional study conducted with 52 children with CZS (GZ) compared with 25 healthy children (CG). Clinical evaluation, EKG, and echocardiogram were performed in all of them. Also, troponin I and natriuretic peptide type B (BNP) dosages were performed in GZ. Results: The median age of the studied population was 5 years in groups, GZ (3 to 6 years), CG (3 to 8 years), 40.4% (GZ) and 60% (CG) of female gender. The most prevalent electrocardiographic alteration was sinus arrhythmia, GZ: 9 (17.3%) and CG: 4 (16%). The echocardiographic evaluation showed the morphological parameters adjusted for the Z score: left ventricular (LV) end-diastolic diameter in GZ: −2.36 [−5.10, 2.63] vs CG: −1.07 [−3.43, 0.61], p<0.001; LV end-systolic diameter in GZ: −1.02 [−4.49, 0.62] vs CG: −0.06 [−1.98, 2.28], p<0.01; ascending aorta in GZ: −0.09 [−2.08, 1.60] vs CG: 0.43 [−1.47, 2.2], p: 0.021; basal diameter of the right ventricle (RV) in GZ: −2.34 [−4.90, 0.97] vs CG: −0.96 [−2.21, 0.40], p<0.01; pulmonary artery dimension in GZ: −2.13 [−5.99, 0.98] vs CG: −0.24 [−2.53, 0.59], p<0.01. The left atrium volume index (ml/m 2 ) was in GZ: 13.15 [6.80, 18.00] vs CG: 18.80 [5.90, 25.30], p<0.01; right atrium volume index (ml/m 2 ) in GZ: 10.10 [4.90, 15.30] vs CG: 15.80 [4.10, 24.80], p<0.01. The septum systolic excursion of the mitral annular plane (MAPSE, cm) was in GZ: 0.98 [0.78, 1.66] vs CG: 1.25 [1.07, 1.56], p<0.01; and lateral annulus: 1.25 [0.81, 1.86] vs CG: 1.46 [1.07, 1.83], p<0.001; tricuspid annular plane systolic excursion (cm) in GZ: 1.52 [1.13, 2.34] vs CG: 1.90 [1.62, 2.35], p<0.01; S' of the RV (cm/s) was in GZ: 10.60 [6.49, 21.00] vs CG: 12.80 [9.19, 16.20], p<0.01. The peak of late mitral inflow (A wave, cm/s) was in GZ: 64 [24, 134] vs CG: 52 [26, 94], p=0.02; peak of late diastolic mitral annular wave (e') of septum (cm/s) was GZ: 15 [7, 23] vs CG: 17 [12, 27], p<0.01; peak of e' lateral (cm/s) was in GZ: 11 [7, 19], CG: 12 [9, 15], p<0, 016; E/e' ratio was GZ: 7.52 [4.57, 10.78] vs CG: 6.41 [4.75, 12.64], p<0.01. The LV longitudinal and circumferential and RV longitudinal strain measurements showed no difference between the groups. Conclusion: A reduction in cardiac dimensions and biventricular dysfunction was found in CZS, showing an early cardiac impairment, which will enable to establishment early therapies, avoiding severe heart failure. Funding Acknowledgement: Type of funding sources: None.